2022
DOI: 10.1021/acs.jafc.2c03990
|View full text |Cite
|
Sign up to set email alerts
|

Covalent and Noncovalent Complexation of Phosvitin and Gallic Acid: Effects on Protein Functionality and In Vitro Digestion Properties

Abstract: To investigate the effects of different binding modes on the structure, function, and digestive properties of the phosvitin (Pv) and gallic acid (GA) complex, Pv was covalently and noncovalently combined with different concentrations of GA (0.5, 1.5, and 2.5 mM). The structural characterization of the two Pv–GA complexes was performed by Fourier transform infrared, circular dichroism, and LC–MS/MS to investigate the covalent and noncovalent binding of Pv and GA. In addition, the microstructure of the two Pv–GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Interestingly, although the addition of phenol can increase the α ‐helix content, the α ‐helix content of the complexes decreased and the random coil content increased with an increase of the added phenol content. This result showed that non‐covalent binding can change the protein's conformation from ordered to disordered 33 …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, although the addition of phenol can increase the α ‐helix content, the α ‐helix content of the complexes decreased and the random coil content increased with an increase of the added phenol content. This result showed that non‐covalent binding can change the protein's conformation from ordered to disordered 33 …”
Section: Resultsmentioning
confidence: 93%
“…This result showed that non-covalent binding can change the protein's conformation from ordered to disordered. 33 Tertiary structures of samples Figure 3 shows the differential effects of phenols with different structures and phenolic hydroxyl groups on the hydrophobic groups of 2S and 13S. As shown in the figure, the addition of phenol can lead to a corresponding reduction in the fluorescence value of proteins, indicating that phenol can interact with the hydrophobic groups (such as Try) of proteins, resulting in fluorescence quenching.…”
Section: Conformational Characterization Of Samples Analysis Of Group...mentioning
confidence: 99%
“…This may be because pepsin and trypsin hydrolyzed myofibrillar protein into small molecule peptides with stronger antioxidant capacity, thus enhancing the antioxidant capacity. Furthermore, after simulated digestion, the network structure and secondary structure of the MP‐C3G conjugates and mixtures were disrupted, and the C3G originally bound to the protein peptide chain was released or exposed, thus enhancing the antioxidant properties 42,43 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, after simulated digestion, the network structure and secondary structure of the MP-C3G conjugates and mixtures were disrupted, and the C3G originally bound to the protein peptide chain was released or exposed, thus enhancing the antioxidant properties. 42,43…”
Section: 2-diphenyl-1-picrylhydrazyl Radical Scavenging Activitiesmentioning
confidence: 99%
“…These mutually supporting results confirmed that the binding method, either noncovalent or covalent, had only a minor effect on the antioxidant properties of MP−Lut samples, whereas the binding amount of Lut played a predominant role. Similarly, digestive results of a phosvitin and the gallic acid complex 56 showed that noncovalent complexes had greater antioxidant and polyphenol protective effects than that of the covalent complexes. In summary, the content of Lut primarily determined the antioxidant capacity of the MP−Lut conjugates, which was dramatically improved compared with that of the control group at higher concentrations of Lut.…”
Section: Quantitation Of the Amount Of Lut Bound To Mpmentioning
confidence: 99%